Design and simulation of microstrip fractal patch antenna. Issue 1 (February 2021) - Nitish Kumar, P; Pavan, R; Suganthi, J; Kavitha, T
Abstract: The proposed fractal antenna is designed to operate at the frequency of 7.23 GHz using an FR4 substrate of relative permittivity of εr = 4.4. Different optimization techniques have been used, such as slots, use of meta-materials, fractal design, Feeding Techniques, to improve some antenna parameters. The resulting fractal design provides a gain of 10 dBi and a return loss of -19.8 dB which is about 90% of the input power radiated.